THE INTERRELATIONSHIP BETWEEN THE PERSONAL VALUE SYSTEM AND PSYCHOLOGICAL DEFENSE MECHANISMS - Nasulloyeva , Shahnoza (INTERNATIONAL CONFERENCE ON SCIENCE, INNOVATION AND GLOBAL DEVELOPMENT, 2026)
This article explores the intrinsic connection between the system of personal values and psychological defense mechanisms based on psycholinguistic and cognitive approaches. It scientifically substantiates that the clarity of the hierarchy of values ensures the internal stability of the individual, while defense mechanisms serve as a "psychological shield" in difficult life situations. Additionally, the impact of social justice and the rule of law on an individual's mental balance is revealed, along with the regulatory functions of values in governing behavior.